Immunogenicity and safety of a second dose of a measles-mumps-rubella vaccine administered to healthy participants 7 years of age or older: A phase III, randomized study. Issue 11 (2nd November 2018) - Abu-Elyazeed, Remon; Jennings, William; Severance, Randall; Noss, Michael; Caplanusi, Adrian; Povey, Michael; Henry, Ouzama
ABSTRACT: The introduction of vaccination programs against measles, mumps, and rubella (MMR) led to significant global reduction in morbidity and mortality from these diseases. The currently recommended MMR vaccination schedule in the United States of America comprises 2 vaccine doses typically administered at 12–15 months and 4–6 years, respectively. Considering recent outbreaks in the USA, catch-up vaccination with an additional dose of MMR vaccine could contribute to outbreak control and community protection. This phase III, observer-blind, randomized controlled trial (NCT02058563) assessed the immunogenicity and safety of a dose of the MMR-RIT vaccine ( Priorix, GSK) compared to MMR II vaccine (control; M-M-R II, Merck&Co Inc.) in ≥7-year-olds who had received ≥1 previous dose of MMR vaccine. We assessed anti-measles, anti-mumps, and anti-rubella antibody geometric mean concentrations (GMCs; primary endpoint) and seroresponse rates (SRRs) at day 42 post-vaccination. Solicited, unsolicited, and serious adverse events (AEs) were recorded. The according-to-protocol cohort for immunogenicity included 869 participants (MMR-RIT: N = 433; MMR II: N = 436). We observed anti-measles, anti-mumps, and anti-rubella antibody GMCs of 1790.2 mIU/mL, 113.5 EU/mL, and 76.1 IU/mL, respectively, and SRRs of 98.8%, 98.4%, and 99.5%, respectively, after a dose of MMR-RIT; non-inferiority compared to MMR II was demonstrated. Both vaccines showed comparable reactogenicity profiles; the most common solicited AEs were injection site redness and pain, and fever (MMR-RIT: 12.2%, 11.8%, and 3.0%; MMR II: 11.7%, 11.5%, and 5.2%, respectively). The dose of MMR-RIT induced robust immune responses that were not inferior to those of MMR II, and was well tolerated.